Resistance of parvalbumin to gastrointestinal digestion is required for profound and long‐lasting prophylactic oral tolerance. Issue 2 (3rd October 2019) - Freidl, Raphaela; Gstöttner, Antonia; Baranyi, Ulrike; Swoboda, Ines; Stolz, Frank; Focke‐Tejkl, Margarete; Wekerle, Thomas; van Ree, Ronald; Valenta, Rudolf; Linhart, Birgit
Abstract: Background: Early introduction of food allergens into children's diet is considered as a strategy for the prevention of food allergy. The major fish allergen parvalbumin exhibits high stability against gastrointestinal digestion. We investigated whether resistance of carp parvalbumin to digestion affects oral tolerance induction. Methods: Natural Cyp c 1, nCyp c 1, and a gastrointestinal digestion‐sensitive recombinant Cyp c 1 mutant, mCyp c 1, were analyzed for their ability to induce oral tolerance in a murine model. Both antigens were compared by gel filtration, circular dichroism measurement, in vitro digestion, and splenocyte proliferation assays using synthetic Cyp c 1‐derived peptides. BALB/c mice were fed once with high doses of nCyp c 1 or mCyp c 1, before sensitization to nCyp c 1. Immunological tolerance was studied by measuring Cyp c 1‐specific antibodies and cellular responses by ELISA, basophil activation, splenocyte proliferations, and intragastric allergen challenge. Results: Wild‐type and mCyp c 1 showed the same physicochemical properties and shared the same major T‐cell epitope. However, mCyp c 1 was more sensitive to enzymatic digestion in vitro than nCyp c 1. A single high‐dose oral administration of nCyp c 1 but not of mCyp c 1 induced long‐term oral tolerance, characterized by lack of parvalbumin‐specific antibody and cellular responses. Moreover, mCyp c 1‐fed mice, but not nCyp c 1‐fed mice developed allergic symptoms upon challenge with nCyp c 1. Conclusion: Sensitivity to digestion in the gastrointestinal tract influences the capacity of an allergen to induce prophylactic oral tolerance. Abstract : The calcium‐binding protein parvalbumin, a major and cross‐reactive allergen for fish allergic patients, induces robust and long‐lasting immunological and clinical oral tolerance in a murine model of fish allergy. A recombinant parvalbumin mutant, that resembled the wild‐type parvalbumin regarding biochemical and immunological properties, but was more sensitive to in vitro digestion, failed to induce oral tolerance. Sensitivity to digestion in the gastrointestinal tract influences the capacity of an allergen to induce prophylactic oral tolerance.